TIME-LAPSE RESERVOIR SURVEILLANCE USING SEISMIC, ROCK PHYSICS AND PRODUCTION DATA OF MIOCENE GROUP I, ANGSI FIELD - REZAEI, SHIBA (2020)
Time-lapse (4D) seismic technology is being used widely in the oil and gas industry to monitor the changes in a reservoir after production begins in a field. 4D seismic data helps to monitor fluid saturation and pore pressure changes through the differences in seismic responses of acquired seismic surveys. Qualitative interpretation of the 4D seismic data shows a combination of changes in the reservoir and the challenge is to quantify fluid saturation and pore pressure-related changes in complex reservoirs. Hence, the main goal of this study is to use two seismic surveys of the baseline (1995) and monitor (2006) to investigate the changes in reservoir properties through post-stack and pre-stack inversion approaches.